A Microbial Signature for Paediatric Perianal Crohn's Disease. (25th February 2022) - Breton, Jessica; Tanes, Ceylan; Tu, Vincent; Albenberg, Lindsey; Rowley, Sarah; Devas, Nina; Hwang, Rosa; Kachelries, Kelly; Wu, Gary D; Baldassano, Robert N; Bittinger, Kyle; Mattei, Peter
Abstract: Background and Aims: Perianal fistulising disease can affect up to 25% of patients with Crohn's disease [CD] and lead to significant morbidity. Although the role of the gut microbiota in inflammatory bowel disease [IBD] has been increasingly recognised, its role in fistula development has scarcely been studied. Here, we aimed to define the microbial signature associated with perianal fistulising CD in children. Methods: A prospective observational study including children age 6-18 years with a diagnosis of perianal fistulising CD was conducted. Stool samples and rectal and perianal fistula swabs were collected. Stool samples and rectal swabs from children with CD without perianal disease and healthy children were included as comparison. Whole shotgun metagenomic sequencing was performed. Results: A total of 31 children [mean age 15.5 ± 3.5 years] with perianal CD were prospectively enrolled. The fistula-associated microbiome showed an increase in alpha diversity and alteration in the abundance of several taxa compared with the rectal- and faecal-associated microbiome with key taxa belonging to the Proteobacteria phylum. Genes conferring resistance to the clinically used antibiotic regimen ciprofloxacin and metronidazole were found in the three sample types. In comparison with children without the perianal phenotype [ N = 36] and healthy controls [ N = 41], the mucosally-associated microbiome of children with perianal CD harboured a reduced butyrogenic potential. Linear discriminant analysis identified key taxa distinguishing the rectal mucosally-associated microbiome of children with perianal CD from children without this phenotype. Conclusions: The microbial community within CD-related anorectal fistula is compositionally and functionally unique. Taken together, these findings emphasise the need to better understand the ecosystem of the fistula milieu to guide development of novel microbiome-based strategies in this CD phenotype.